Autogenic Curvature of Transgressive Shelf Profiles - Junhui Wang; Tetsuji Muto (Geophysical Research Letters)
Abstract Many continental shelves tend to steepen landward. Existing models attribute this curvature to a progressive attenuation of the effect of postglacial sea‐level rise or sediment redistribution by modern coastal‐marine processes. Here, we present an alternative framework in which shelf curvature arises from an inherent self‐organizing mechanism. During sea‐level rise, if the critical length of the downstream alluvial river is exceeded, deltaic sedimentation cannot be sustained. In this non‐deltaic transgressive regime, the alluvial aggradation rate autogenically increases as the river shrinks, enhancing alluvial sediment accumulation and producing a steeper local shelf slope closer to the shoreline. Two‐dimensional geometric modeling reveals a simple governing equation for the self‐organized curvature of the shelf profile, with support from flume‐tank experiments and applications to modern systems, providing a mechanistic basis for interpreting existing shelf profiles.